Digital Skill, Digital Literasi dan Pengaruhnya Terhadap Psikologis Siswa SMP di Kabupaten Bekasi Jawa Barat - Maria Cleopatra; Sara Sahrazad; Yulia Sofiani; Aster Pujaning Ati (Peneliti.net, 2023)
The rapid development of technology makes students have to continue to adapt to various things related to digital. Digital abilities (digital skills) and digital literacy if they are not properly prepared will affect the psychology of students both directly and indirectly. The research method used is a quantitative method. Respondents were 142 junior high school students who attended 2 junior high schools in Bekasi district. The assumption test used is the normality test and homogeneity test. The data is processed with SPSS 20, using tests, and tests. The results of the research are that there is an influence of digital skills on student psychology. There is an influence of digital skills on student psychology and there is an influence of digital skills and digital literacy together on the psychology of junior high school students in Bekasi district, West Java. Children's psychology can be maintained by means of active dialogue and discussion between teachers and children, and parents and students.